Turn-by-turn micro-linguistic analysis of interpreting strategies and communicative functions in Lampung–English virtual tourism encounters - Bungsudi, Bungsudi (Accentia: Journal of English Language and Education, 2025)
This study examined Lampung–English interpreting in a virtual tourism encounter, focusing on how indigenous languages function in online cross-cultural communication. A qualitative single-case study was conducted on a 20-minute Zoom session involving a native Lampung speaker, an English-speaking participant, and a bilingual student interpreter. The conversation was transcribed and analyzed thematically to identify interpreting strategies and their communicative roles. Findings revealed three main strategies: (1) literal translation with retention of local place names to ensure accuracy, (2) retention combined with short explanations to clarify culture-specific terms, and (3) pragmatic adaptation to align messages with international tourism discourse. These strategies served different functions, including providing information, promoting culture, and building rapport. Micro-level analysis also showed how interpreters used word choices, cohesion, and additional explanations to overcome the lack of visual cues in online communication. The study introduced a simple framework: accuracy, culture, and audience, which explains how interpreters balance factual precision, cultural authenticity, and audience expectations. This highlights the interpreter’s role not only as a language mediator but also as a cultural ambassador in digital tourism. The study contributes to the limited research on indigenous language interpreting, while offering practical insights for interpreter training, curriculum design, and the promotion of local culture through virtual tourism.